Pork as a source of transmission of Toxoplasma gondii to humans: a parasite burden study in pig tissues after infection with different strains of Toxoplasma gondii as a function of time and different parasite stages. Issue 7 (June 2018) - Gisbert Algaba, Ignacio; Verhaegen, Bavo; Jennes, Malgorzata; Rahman, Mizanur; Coucke, Wim; Cox, Eric; Dorny, Pierre; Dierick, Katelijne; De Craeye, Stéphane
Graphical abstract: Highlights: There was no significant effect of the Tosoplasma gondii strains used on the parasite burden in pigs. Heart and brain are the most parasitised tissues during the chronic phase of T. gondii infection. A decreasing parasite burden in lungs as a function of time was observed in pigs after T. gondii infection. Already at day 4 after infection the parasite can be found in both heart and lungs. There is a potential effect of the parasite stage on the parasite burden. Abstract: Toxoplasma gondii is an ubiquitous apicomplexan parasite which can infect any warm-blooded animal including humans. Humans and carnivores/omnivores can also become infected by consumption of raw or undercooked infected meat containing muscle cysts. This route of transmission is considered to account for at least 30% of human toxoplasmosis cases. To better assess the role of pork as a source of infection for humans, the parasite burden resulting from experimental infection with different parasite stages and different strains of T. gondii during the acute and chronic phases was studied. The parasite burden in different tissues was measured with a ISO 17025 validated Magnetic Capture-quantitative PCR. A high burden of infection was found in heart and lungs during the acute phase of infection and heart and brain were identified as the most parasitised tissues during the chronic phase of infection, independent of the parasite stage and the strain used. Remarkably, a higher parasite burden was measured in different tissues following infection with oocysts of a type II strain compared with a tissue cyst infection with three strains of either type II or a type I/II. However, these results could have been affected by the use of different strains and euthanasia time points. The parasite burden resulting from a tissue cyst infection was not significantly different between the two strains.